Genetic Predisposition to Coronavirus Disease 2019 in Relation to Ten Cardiovascular Conditions: A Two-Sample Mendelian Randomization Study - Jia, Min; Chen, He-Jia; Jia, Ling-Mei; Chen, Ya-Li (Frontiers in Medicine, 2022)
Background: The long-term health consequences of COVID-19 remain largely unclear. The aim of this study was to apply the Mendelian randomization (MR) design to estimate the causal associations between COVID-19 and 10 cardiovascular conditions. Methods: Single-nucleotide polymorphisms associated with COVID-19 (published in 2020) were used as instrumental variables to estimate the causal effect of COVID-19 on 10 cardiovascular conditions (obtained from FinnGen project, which launched in Finland in the autumn of 2017). The random-effects inverse-variance weighted (IVW) method was conducted for the main analyses with a complementary analysis of the weighted median and MR-Egger approaches. Results: In the IVW analysis, genetically predicted COVID-19 was suggestively associated with major coronary heart disease event (OR 1.081; 95% CI 1.007–1.160; P=0.045) and heart failure (OR 1.049; 95% CI 1.001–1.100; P=0.045) with similar estimates in weighted median regressions. No directional pleiotropic effects were observed in both funnel plots and MR-Egger intercepts. Conclusions/interpretation: Our findings provide direct evidence that patients infected with COVID-19 are causally associated with increased risk of cardiovascular disease, especially for major coronary heart disease event and heart failure.